On the 3 1 Π u state in caesium dimer - Szczepkowski, Jacek; Grochola, Anna; Jastrzebski, Wlodzimierz; Kowalczyk, Pawel (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2021)
Polarisation labelling spectroscopy technique was employed to study the 3 Π state of Cs molecule. The main equlibrium constants are T =20684.56cm ,ω =30.62 cm and R =5.27 Å. Vibrational levels v=4-35 of the 3 Π state were found to be subject to strong perturbations by the neighbouring electronic states. Energies of 3352 rovibronic levels of the perturbed complex were determined.